PrimOER: Professionalisierung und Erweiterung der OER-Community Grundschulpädagogik im Kontext von Inklusion und Chancengerechtigkeit in der Primarstufenlehrkräftebildung. Beitrag am ORCA.nrw-Fachtag im Rahmen des OER-Festival 2024 Essen. - Büker, Petra; Herding, Jana; Henning, Charleen; Basten, Nina Celine; Kamin, Anna-Maria; Jaenke, Vanessa; Bruhnke, Lorena; Oevel, Gudrun; Knurr, Moritz

Inklusive chancengerechte Bildung im Grundschullehramt mit OER und OEP gestalten? Probleme, Diskurse, Perspektiven. Eröffnungsvortrag im Rahmen der PrimOER-Auftaktveranstaltung: OER-Erfahrungen und OEP-Formate in der inklusiven Grundschullehrkräftebildung. Universität Paderborn (online). - Büker, Petra; Kamin, Anna-Maria

Editorial: Lehrer:innenbildung unter der Perspektive von Inklusion und Digitalisierung. Mit Offenen Bildungsressourcen (OER) zu offenen, innovativen Bildungspraktiken (OEP) - Glawe, Katrin; Kamin, Anna-Maria; Herding, Jana; Büker, Petra (MedienPädagogik. Zeitschrift für Theorie und Praxis der Medienbildung)

„Inklusion vom Kind aus denken. Partizipative Schulkulturen gestalten“ Vortrag im Rahmen der PPIK-Forschungsreihe (Paderborner Perspektiven auf Inklusion), Universität Paderborn. - Büker, Petra; Herding, Jana

Evaluation eines Stressbewältigungsseminars im Hochschulkontext - Decker, Claudia; Watson, Christina; Meier, Jana; Hüttemann, Lukas (Die psycho-soziale Situation von Studierenden in der (post-)pandemischen Zeit - Stand der Forschung und Impulse aus der Praxis)

Volkert, Klaus, „Drei mathematische Freunde über Poincaré“, Philosophia Scientiæ 27.3 (2023), 129–159. - Peckhaus, Volker (zbMATH Open, Zbl. 1542.01013)

Braverman, Charles and Jules-Henri Greber, « P. Tannery : Le lien entre les mathématiques et la Revue philosophique », Revue d’histoire des mathématiques 28 (2022), 117–146. - Peckhaus, Volker (zbMATH Open, Zbl. 1536.01005)

Gillies, Donald, Lakatos and the Historical Approach to Philosophy of Mathematics (Cambridge Elements. Elements in the Philosophy of Mathematics), Cambridge University Press: Cambridge 2023, 60 S. - Peckhaus, Volker (zbMATH Open, Zbl. 1536.01001)

Paseau, A. C./Wesley Wrigley, The Euclidean Programme (Cambridge Elements. Elements in the Philosophy of Mathematics), Cambridge University Press: Cambridge 2024, 74 S. - Peckhaus, Volker (ZbMath Open, Zbl. 1542.00017)

Sutherland, Daniel, Kant’s Mathematical World. Mathematics, Cognition, and Experience, Cambridge University Press: Cambridge 2022 - Peckhaus, Volker (zbMATH Open, Zbl. 1537.01003)

Morscher, Edgar, Bernard Bolzano’s System der Philosophie (Bernard Bolzano-Gesamtausgabe. Einleitungsband, Tl. 3), Frommann-Holzboog Verlag, Eckhart Holzboog: Stuttgart-Bad Cannstatt 2024. - Peckhaus, Volker (zbMATH Open, Zbl. 1533.01004)

Interdisciplinary and Collaborative Training in Neuroscience: Insights from the Human Brain Project Education Programme - Geminiani, Alice; Kathrein, Judith; Yegenoglu, Alper; Vogel, Franziska; Armendariz, Marcelo; Ben-Zion, Ziv; Bogdan, Petrut Antoniu; Covelo, Joana; Diaz Pier, Marissa; Grasenick, Karin; Karasenko, Vitali; Klijn, Wouter; et al. (Neuroinformatics)
Abstract Neuroscience education is challenged by rapidly evolving technology and the development of interdisciplinary approaches for brain research. The Human Brain Project (HBP) Education Programme aimed to address the need for interdisciplinary expertise in brain research by equipping a new generation of researchers with skills across neuroscience, medicine, and information technology. Over its ten year duration, the programme engaged over 1,300 experts and attracted more than 5,500 participants from various scientific disciplines in its blended learning curriculum, specialised schools and workshops, and events fostering dialogue among early-career researchers. Key principles of the programme’s approach included fostering interdisciplinarity, adaptability to the evolving research landscape and infrastructure, and a collaborative environment with a focus on empowering early-career researchers. Following the programme’s conclusion, we provide here an analysis and in-depth view across a diverse range of educational formats and events. Our results show that the Education Programme achieved success in its wide geographic reach, the diversity of participants, and the establishment of transversal collaborations. Building on these experiences and achievements, we describe how leveraging digital tools and platforms provides accessible and highly specialised training, which can enhance existing education programmes for the next generation of brain researchers working in decentralised European collaborative spaces. Finally, we present the lessons learnt so that similar initiatives may improve upon our experience and incorporate our suggestions into their own programme.

Determinanten und Typen phasenübergreifenden Transfers in Communities of Practice der Lehrkräftebildung - Niemann, Jan; Raneck-Kuhlmann, A.; Eickelmann, Birgit; Drossel, Kerstin; Buhl, Heike M. (Lehrkräftebildung in der digitalen Welt – zukunftsorientierte Forschungs- und Praxisperspektiven)

Elterliche Unterstützung beim Lernen mit digitalen Medien - Kamin, Anna-Maria; Meister, Dorothee M.; Buhl, Heike M. (Medien - Bildung - Forschung. Integrative und interdisziplinäre Perspektiven)

Simultaneous Diarization and Separation of Meetings through the Integration of Statistical Mixture Models - Cord-Landwehr, Tobias; Boeddeker, Christoph; Haeb-Umbach, Reinhold (ICASSP 2025 - 2025 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
We propose an approach for simultaneous diarization and separation of meeting data. It consists of a complex Angular Central Gaussian Mixture Model (cACGMM) for speech source separation, and a von-Mises-Fisher Mixture Model (VMFMM) for diarization in a joint statistical framework. Through the integration, both spatial and spectral information are exploited for diarization and separation. We also develop a method for counting the number of active speakers in a segment of a meeting to support block-wise processing. While the total number of speakers in a meeting may be known, it is usually not known on a per-segment level. With the proposed speaker counting, joint diarization and source separation can be done segment-by-segment, and the permutation problem across segments is solved, thus allowing for block-online processing in the future. Experimental results on the LibriCSS meeting corpus show that the integrated approach outperforms a cascaded approach of diarization and speech enhancement in terms of WER, both on a per-segment and on a per-meeting level.
Keywords: diarization; source separation; mixture model; meeting

Geodesic Interpolation of Frame-Wise Speaker Embeddings for the Diarization of Meeting Scenarios - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (ICASSP 2024 - 2024 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Isostructural Series of a Cyclometalated Iron Complex in Three Oxidation States - Steube, Jakob; Fritsch, Lorena; Kruse, Ayla; Bokareva, Olga S.; Demeshko, Serhiy; Elgabarty, Hossam; Schoch, Roland; Alaraby, Mohammad; Egold, Hans; Bracht, Bastian Johannes; Schmitz, Lennart; Hohloch, Stephan; et al. (Inorganic Chemistry)
An isostructural series of FeII, FeIII, and Fe(IV)complexes [Fe(ImP)2]0/+/2+ utilizing the ImP 1,1′-(1,3-phenylene)-bis(3-methyl-1-imidazol-2-ylidene) ligand, combining N-heterocy-clic carbenes and cyclometalating functions, is presented. The strong donor motif stabilizes the high-valent Fe(IV) oxidation state yet keeps the FeII oxidation state accessible from the parent Fe(III)compound. Chemical oxidation of [Fe(ImP)2]+ yields stable [FeIV(ImP)2]2+. In contrast, [FeII(ImP)2]0, obtained by reduction,is highly sensitive toward oxygen. Exhaustive ground state characterization by single-crystal X-ray diffraction, 1H NMR,Mössbauer spectroscopy, temperature-dependent magnetic measurements, a combination of X-ray absorption near edge structureand valence-to-core, as well as core-to-core X-ray emission spectroscopy, complemented by detailed density functional theory (DFT) analysis, reveals that the three complexes[Fe(ImP)2]0/+/2+ can be unequivocally attributed to low-spin d6, d5, and d4 complexes. The excited state landscape of the Fe(II) and Fe(IV) complexes is characterized by short-lived 3MLCT and 3LMCT states, with lifetimes of 5.1 and 1.4 ps, respectively. In the FeII-compound, an energetically low-lying MC state leads to fast deactivation of the MLCT state. The distorted square-pyramidal state, where one carbene is dissociated, can not only relax into the ground state, but also into a singlet dissociated state. Its formation was investigated with time-dependent optical spectroscopy, while insights into its structure were gained by NMR spectroscopy.
Keywords: Photo

Ultrafast Two‐Color X‐Ray Emission Spectroscopy Reveals Excited State Landscape in a Base Metal Dyad - Nowakowski, Michał; Huber‐Gedert, Marina; Elgabarty, Hossam; Kalinko, Aleksandr; Kubicki, Jacek; Kertmen, Ahmet; Lindner, Natalia; Khakhulin, Dmitry; Lima, Frederico A.; Choi, Tae‐Kyu; Biednov, Mykola; Schmitz, Lennart; et al. (Advanced Science)
Effective photoinduced charge transfer makes molecular bimetallic assemblies attractive for applications as active light‐induced proton reduction systems. Developing competitive base metal dyads is mandatory for a more sustainable future. However, the electron transfer mechanisms from the photosensitizer to the proton reduction catalyst in base metal dyads remain so far unexplored. A Fe─Co dyad that exhibits photocatalytic H2 production activity is studied using femtosecond X‐ray emission spectroscopy, complemented by ultrafast optical spectroscopy and theoretical time‐dependent DFT calculations, to understand the electronic and structural dynamics after photoexcitation and during the subsequent charge transfer process from the Fe(II) photosensitizer to the cobaloxime catalyst. This novel approach enables the simultaneous measurement of the transient X‐ray emission at the iron and cobalt K‐edges in a two‐color experiment. With this methodology, the excited state dynamics are correlated to the electron transfer processes, and evidence of the Fe→Co electron transfer as an initial step of proton reduction activity is unraveled.
Keywords: Photo; Xray

Insights into the First Multi-Transition-Metal Containing Ruddlesden Popper-Type Cathode for all-solid-state Fluoride Ion Batteries - Vanita, Vanita; Waidha, Aamir Iqbal; Vasala, Sami; Puphal, Pascal; Schoch, Roland; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver (Journal of Materials Chemistry A)
Promising cathode materials for fluoride-ion batteries (FIBs) are 3d transition metal containing oxides with Ruddlesden-Popper-type structure. So far, multi-elemental compositions were not investigated, but could alternate electrochemical performance similar to what has been found for cathode materials for lithium-ion batteries. Within this study, we investigate RP type La2Ni0.75Co0.25O4.08 as an intercalation-based active cathode material for all-solid-state FIBs. We determine the structural changes of La2Ni0.75Co0.25O4.08 during fluoride intercalation / de-intercalation by ex-situ X-ray diffraction, which showed that F- insertion leads to transformation of the parent phase to three different phases. Changes in Ni and Co oxidation states and coordination environment were examined by X-ray absorption spectroscopy and magnetic measurements in order to understand the complex reaction behaviour of the phases in detail, showing that the two transition metals behave differently in the charging and discharging process. Under optimized operating conditions, a cycle life of 120 cycles at a critical cut-off capacity of 40 mAh g-1 against Pb/PbF2 was obtained, which is one of the highest observed for intercalation electrode materials in FIBs so far. The average Coulombic efficiencies ranged from 85% to 90%. Thus, La2Ni0.75Co0.25O4.08 could be a promising candidate for cycling-stable high-energy cathode materials for all-solid-state FIBs
Keywords: Xray

Hydrogen spillover through hydride transfer: the reaction of ZnO and ZrO2 with strong hydride donors - Benz, Michael; Bunjaku, Osman; Nowakowski, Michał; Allgaier, Alexander; Biswas, Indro; van Slageren, Joris; Bauer, Matthias; Estes, Deven P. (Catalysis Science & Technology)
Hydride donors such as DIBAL or CuH react with ZnO and ZrO2 via hydrogen spillover. This suggests that hydrogen spillover in catalysts based on these metal oxides may take place via initial hydride transfer and not via proton–electron transfer.
Keywords: Xray